RANCANG BANGUN APLIKASI REKAM MEDIS RAWAT JALAN BERBASIS DEKSTOP MENGGUNAKAN METODE PROTOTIPE - - Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Nusa Mandiri, Yustina Meisella Kristania (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Rapid technological development at this time encourages people to use technology. The use of technological tools today has led to all aspects of life, including the world of health which has become a necessity for society in general. The health service sector utilizes information technology to enter medical record data. Medical record is a medical record of a patient that contains all information relating to the health of the patient, medical records are used as a basis for determining further action by the doctor on handling patient health problems in health care agencies. At Amanda Primary Clinic, medical record data is still stored on paper media. Maintenance of medical records becomes more difficult as the number of medical record data continues to increase. In this final project developed a desktop-based outpatient medical record application. Needs analysis is done by the method of developing the prototipe model software and data collection techniques used are observation, interviews and literature study. Outpatient medical record application was developed to manage patient data and patient medical records. The application can be used by doctors and medical professionals at Amanda Primary Clinic to manage patient medical record data